652. Ceftazidime-avibactam Alone or as Combination Therapy? Multicenter Retrospective Cohort Analysis of Clinical Outcomes in Patients with Carbapenem-resistant Gram-negative Infection. (15th December 2022) - Mishuk, Ahmed Ullah; Strich, Jeffrey R; Warner, Sarah; Sun, Junfeng; Malik, Seidu; Lawandi, Alexander; Kondo, Maiko; Satlin, Michael J; Chandorkar, Aditya; Heil, Emily L; Morales, Megan K; Mathur, Anisha; et al.
Abstract: Background: Ceftazidime-avibactam (caz-avi), a novel β-lactam/β-lactamase inhibitor, is commonly utilized for carbapenem-resistant gram-negative infections (CR-GNI). However, the benefits vs risks of combining caz-avi with other agents are unclear. Methods: In this retrospective cohort study, inpatients with CR-GNI treated with caz-avi were identified at 9 U.S. hospitals. The impact of caz-avi monotherapy (MT) or combination therapy (CT; i.e., any concomitant use of gram-negative-active antibiotics) was studied using logistic regression, controlling for baseline patient and hospital factors. The primary outcome was in-hospital mortality or discharge to hospice (death), and secondary outcomes were length of stay (LOS), resolution of infectious signs and symptoms (clinical response), 90-day recurrent infection and future caz-avi–resistant organism. An adjusted odds ratio (aOR) with 95% confidence interval (CI) was used to assess the primary and secondary outcomes. Results: 328/499 (65.7%) patients received caz-avi as targeted therapy for a CR-GNI. Overall patients treated with MT and CT were similar at baseline and had comparable baseline demographics although patients treated with CT were more likely to be in the ICU and receive a concomitant empiric in vitro-concordant antibiotic (table 1). The most common organism was K lebsiella spp. (44.6%) followed by Pseudomonas aeruginosa (27.7%) (table 2). Concomitant gram-negative agents are shown in table 3. Overall, 92 (28.1%) patients died and CT (vs MT) displayed similar adjusted mortality risk (27.7% vs 28.7%; aOR [95%CI]: 0.67 [0.34-1.33]) and LOS (19 [9, 37] and 20 [9, 42.5] days). CT (vs MT) was associated with greater odds of clinical response (aOR: 2.25 [95%CI:1.15-4.41]). Among survivors, similar rates of 90-day recurrent infection (50/154 (32.5%) were observed in CT vs 18/82 (22.0%) in MT group (p=0.09) and 5 (2.19%) patients had future infection with a caz-avi–resistant pathogen (3 in CT and 2 in MT group). Conclusion: Compared to patients with CR-GNI treated with caz-avi alone, those who received CT including caz-avy had similar survival and LOS but higher clinical response. The role of CT in the era of novel antibiotics warrants additional study. Disclosures: Helen W. Boucher, MD, American Society of Microbiology: Honoraria|Elsevier: Honoraria|Sanford Guide: Honoraria.